A Deductive Analysis of Public Private Partnerships for Health Technology - Montpetit, Eric (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2006)
In several countries, consulting firms, think thanks and even government agencies spend a considerable amount of energy trying to expand the scope of public private partnerships (PPPs). Initially confined to the construction and maintenance of public infrastructures, PPPs are currently discussed and experimented with in sectors as diverse as health care provision, crime reduction, immigrants’ integration and even the organization of elections. This paper discusses the way PPPs are likely to transform the adoption of novel medical technology in countries where health care is publicly funded. I believe, however, that several ideas presented here can be useful to consider in applying PPPs to all sectors of state intervention relying on expensive technologies. In the first section, I begin by presenting the economic understanding upon which PPPs rest. I then present the simple and uncontroversial assumption that, in democratic countries, PPPs are negotiated by politicians. Withholding the rationality assumption upon which economic theory rests, I argue that rational politicians are unlikely to prefer a PPP contract appealing to a private partner, unless politicians accept occasional renegotiation of given clauses of PPP contracts. Where this occurs, however, the alleged economic efficiency of PPPs is seriously undermined. In the second section, I present a series of reasons to contest economic theory’s treatment of health technology choices as economic choices. These reasons, I suggest, made significant contributions to health technology assessment and purchase reforms. The economic reasoning behind PPPs, I conclude, poses a serious threat to these reforms.